(untitled) (TAMADDUN NURI JURNALI, 2024)
A work of art is a product of the writer’s thinking, in which the artist’s talent, skill, worldview, the rules of literature and the writer’s style are embodied. The theme and content of a work of art are directly related to the social period in which the work was created, as well as the writer’s mentality. That’s why the writer can’t write effectively about things and events that he hasn’t seen or felt.